Variations in Opinions toward Disclosure Trend of Insurance Companies in Bangladesh: An Empirical Study - Siddique, Md. Abu Bokar; Neogy, Taposh Kumar; Islam, Md. Rabiul (American Journal of Trade and Policy, 2014)
The study is an attempt to examine empirically the perceptions of a sample of users of reported information regarding the use of annual reports for decision making, adequacy, reliability, consistency, comparability, relevance, satisfaction and compliance of BASs (IASs) in preparing annual report. Results of the study demonstrated that there is a lack of disclosure in the annual reports of insurance companies. The study also found insigniﬁ cant variations in opinions towards adequacy, consistency, relevance, satisfaction and compliance of provisions of Bangladesh Accounting Standards in disclosure policy of the companies while there are signiﬁ cant variations in responses regarding reliability and comparability of accounting information disclosed in the annual reports. Insurance companies should develop their reporting policy to satisfy their users through compliance the disclosure requirements of international standards.
Keywords: Financial disclosure; Insurance company; Bangladesh